Peran Pekerja sosial dalam Bimbingan Psikososial ADL untuk Menumbuhkan Kemandirian Penerima Manfaat Psikotik Ringan di Balai Rehabilitasi PMKS Sidoarjo - Purnama Sari, Citra; Widodo (J+PLUS UNESA, 2025)
This study describes the role of social workers in psychosocial guidance related to Activities of Daily Living (ADL) to foster independence among beneficiaries with mild psychotic disorders at Balai PMKS Sidoarjo. The research employs a descriptive qualitative method, with social workers and beneficiaries participating in the ADL psychosocial guidance program as the study subjects. Data were collected through in-depth interviews, observations, and document analysis. To ensure data validity, the study applied credibility, dependability, confirmability, and transferability tests. Research shows that social workers have several important roles (1) Facilitator, They assess needs, create schedules, provide necessary resources, and design skill-learning materials. (2) Motivator, They offer emotional support and encourage progress. (3) Counselor, They provide one-on-one counseling and ongoing support. (4) Advocate, They help beneficiaries access essential services like psychiatrists, doctors, and social institutions. (5) Protector, They create a safe and supportive environment, offering psychological help and protection. Psychosocial support plays a big role in helping people with mild psychotic conditions become more independent. ADL (Activities of Daily Living) training helps them manage daily tasks on their own while also improving their social skills and confidence. Keywords: Social Workers, Beneficiaries, Psychosocial Guidance, Activities of Daily Living, Independence.